Gastrografin in Prolonged Postoperative Ileus: A Double-blinded Randomized Controlled Trial. Issue 1 (July 2015) - Vather, Ryash; Josephson, Rachel; Jaung, Rebekah; Kahokehr, Arman; Sammour, Tarik; Bissett, Ian
Abstract : Objective: To investigate the therapeutic value of Gastrografin in shortening duration of prolonged postoperative ileus (PPOI) after elective colorectal surgery. Background: Gut wall edema is central to the pathogenesis of PPOI. Hyperosmotic, orally administered, water-soluble contrast media such as Gastrografin are theoretically capable of mitigating this edema. Methods: A double-blinded, placebo-controlled, randomized trial was conducted. Participants were allocated to receive 100 mL of Gastrografin (Exposure Group) or flavored distilled water (Control Group) administered enterally. Other aspects of management were standardized. Resolution of PPOI was assessed 12-hourly. Results: Eighty patients were randomized equally, with 5 in the Exposure Group and 4 in the Control Group excluded from analysis. Participants were evenly matched at baseline. Mean duration of PPOI did not differ between Exposure and Control Groups (83.7 vs 101.3 hours; P = 0.191). When considering individual markers of PPOI resolution, Gastrografin did not affect time to resolution of nausea and vomiting (64.5 vs 74.3 hours; P = 0.404) or consumption of oral diet (75.8 vs 90.0 hours; P = 0.297). However, it accelerated time to flatus or stool (18.9 vs 32.7 hours; P = 0.047) and time to resolution of abdominal distension (52.8 vs 77.7 hours; P = 0.013). There were no significant differences between groups in nasogastric output; analgesia, antiemetic, or fluid requirement; complications; or length of stay. Conclusions: Gastrografin is not clinically useful in shortening an episode of PPOI characterized by upper and lower gastrointestinal symptoms. It may however be of therapeutic benefit in the subset of PPOI patients who display lower gastrointestinal symptoms exclusively after surgery. Abstract : Supplemental Digital Content is Available in the Text.This randomized controlled trial investigated the therapeutic value of Gastrografin in shortening duration of prolonged ileus. Gastrografin reduced the time taken to passage of flatus or stool and resolution of distension, but not the time taken to tolerance of an oral diet or resolution of nausea and vomiting.